White egrets poems - Walcott, Derek (New York Farrar, Straus and Giroux, 2011)
In this work, the poet treats the characteristic subjects of his career, the Caribbean's complex colonial legacy, his love of the Western literary tradition, the wisdom that comes through the passing of time, the always strange joys of new love, and the sometimes terrifying beauty of the natural world, with an intensity and drive that recall his greatest work. Through the mesmerizing repetition of theme and imagery, he creates an almost surf like cadence, broadening the possibilities of rhyme and meter, poetic form and language. This work is a moving new collection from one of the most important poets of the twentieth century, a celebration of the life and language of the West Indies. It is also a triumphant paean to beauty, love, art, and, perhaps most surprisingly, getting older.
White egrets -- The acacia trees -- Sicilian suite -- Spanish series -- In Italy -- The lost empire -- The spectre of empire -- Pastoral -- A London afternoon -- In the village -- The Sweet Life Cafe -- A sea-change -- On Capri -- Sixty years after -- In Amsterdam -- Forty acres -- Epithalamium: the rainy season -- Barcelona -- Elegy.
Keywords: Poetry